PERAN KEPEMIMPINAN PARTISIPATIF DAN ETOS KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI MOTIVASI KERJA DI SATUAN POLISI PAMONG PRAJA DAN KEBAKARAN KAB. KONAWE KEPULAUAN - Ridha Fadhilah Kamaruddin; Adnan Hakim; Muhammad Masri; Dzulfikri Azis Muthalib (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the effect of digital marketing on property purchasing This study aims to understand and explain the Effect of Participative Leadership and Work Ethic on Employee Performance with the Mediation of Work Motivation at the Civil Service Police Unit and Fire Department. The population in this study consists of ASN (Civil Servant) employees of the Civil Service Police Unit and Fire Department, totaling 102 people. To assist in the data processing within this study, the software tool Partial Least Squares (PLS) 4.0 was used as the analytical tool. The results of this study indicate that participative leadership has a positive and significant effect on work motivation. Work ethic has a positive and significant effect on work motivation. Work motivation has a positive and significant effect on employee performance. Participative leadership has a positive and insignificant effect on employee performance. Work ethic has a positive and significant effect on employee performance. Work motivation serves as a full mediation variable in the relationship between participative leadership and employee performance. Work motivation serves as a partial mediation variable in the relationship between work ethic and employee performance.